Collaborative Management Partnership Toolkit - World Bank (World Bank, Washington, DC, 2021)
Protected areas conserve nature and support livelihoods and economies, yet they are undervalued and underfunded. In Africa, 40 co-management and delegated collaborative management partnerships (CMPs) have been established by 15 governments. An analysis of these 40 CMPs in the CMP Toolkit shows that CMPs help fund protected area management enabling the delivery of positive conservation, social, and economic outcomes. This Toolkit is one of the most comprehensive reviews of CMPs in Africa and serves as a reference guide for governments and implementing partners who are considering CMPs as a way to address challenges and threats to protected areas and wildlife. While the case studies and lessons in the Toolkit are derived from national protected areas in Africa, it can be applied to private and community protected areas as well as other protected areas around the world.